Evolutionary and Physiological Adaptation of Pseudomonas aeruginosa to Elevated Concentrations of Sodium Chloride - Taha, Mariam (Université d'Ottawa / University of Ottawa, 2011)
I have investigated the evolutionary response of Pseudomonas aeruginosa to salt (NaCl) stress, and the physiological mechanisms responsible for this adaptation. Populations of P. aeruginosa founded from the same ancestral genotype were selected at three different concentrations of NaCl, low, moderate and high for about 660 generations with four independent replicates for each concentration. Adaptation was measured as the fitness of the evolved populations relative to the ancestor assessed in direct, head-to-head competition experiments conducted in the same environment in which they were selected (direct response) as well as in all alternative environments (correlated response). Results suggest that selection in each salt environment led to adaptation to that environment and a modest degree of specialization that evolved because correlated responses to selection were smaller than direct responses. In order to identify the physiological mechanisms contributing to the populations' adaptation in high NaCl concentration, I chose a sample of evolved lines that showed the strongest evidence for specialization to salt and competed them against the common ancestor in KCl and sucrose. Results suggested that increased Na+ /H+ antiporter activity is probably the primary mechanism behind adaptation to high NaCl concentration, however alternative mechanisms cannot be excluded. Tolerance curves, which measure the performance of a genotype across a gradient of salt concentrations, suggested no change in the high salt group’s ability to tolerate extreme concentrations of NaCl. We conclude that high salt evolved population showed improvements to its ionic/osmotic stress resistance strategies mainly to Na+ efflux strategies but with no changes to salt niche.
Keywords: Bacteria; Sodium Chloride; Evolution; Adaptation; Pseudomonas aeruginosa